Nature inspired metal-organic frameworks: Challenges, innovations, and prospects - Joseph, Annlyn Mary; Pramodh, Mahika; Thomas, Noel Abraham; Ramyashree, M. S.; Priya, S. Shanmuga; Sudhakar, K.; Tahir, Muhammad Suleman (Elsevier B.V., 2025)
This study investigates the synthesis, application, and prospective advancements of bio-inspired materials, with a particular emphasis on Metal-Organic Frameworks (MOFs). These biomimetic MOFs, which emulate the catalytic mechanisms of natural enzymes, exhibit superior performance in diverse domains. The research demonstrates the exceptional catalytic efficacy, selectivity, and sustainability of bio-inspired MOFs, driven by their unique structural and functional properties. However, significant challenges persist, including high synthesis and development costs, scalability limitations, and the necessity for thorough biocompatibility and environmental impact assessments. Addressing these challenges demands interdisciplinary collaboration and innovative methodologies in the design and fabrication of bio-inspired materials. The study concludes that, despite the substantial opportunities presented by bio-inspired MOFs for technological innovation and sustainability, overcoming the existing technical and economic barriers is crucial for their broader implementation.